Study of electronic patient records in a selected government hospital in Manila implications of a paperless recordkeeping system - Yap, Joseph M. (Institute of Library and Information Science, University of the Philippines Diliman, 2006)
This study provides an overview of the implications created by a paperless recordkeeping system. In the advent of new technology occurs numerous fundamental issues associated with the use and proliferation of electronic patient records. Electronic Patient Records (EPR) replaces the manual form of recordkeeping in a traditional paper-based format.